Use of metal in stems and acrylic treating cervical stenosis and atresia and sterility - Bunster, Eduardo (2015)
The use of intrauterine stem gold, silver or acrylic today is a safe procedure. Its use is especially recommended for spasmodic uterine dysmenorrhea cause, uterine hypoplasia atresia and stenosis of the neck, and uterine hiperanteflexiones in certain conditional sterility or cryptogenic causes cervical factors. It insists on the advantages of using an original model of the author who has been specially designed to correct sterility. Stems made of rubber (rubber) should be outlawed. The results obtained in 40 cases where it was possible to cure sterility in 30% of 22 infertile patients are presented, dysmenorrhea 71% from 9 patients and cervical atresia or body in 88% of another 9 ill. In half the patients a discrete and painless one ovary of which is attributed to pituitary gonadotropins discharge caused by a reflection growth cervical match it was found.